UKURAN PERUSAHAAN, UMUR PERUSAHAAN, PROFITABILITAS DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) ( Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode 2014 – 2016 ) - Meiti Suri Utami, 14.05.52.0013; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
This study aims to obtain empirical evidence of firm size, firm age, profitability and leverage against tax avoidance proxyed by Cash Effective Tax Rate (CETR). Independent variables in this study are firm size, company age, profitability and leverage, while the dependent variable is tax avoidance. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) period 2014-2016. The sample in this study was chosen using Purposive sampling method and obtained by 109 sample observation. Analytical techniques used in this study are descriptive statistics, classical assumption test and multiple linear regression analysis.The result of analysis shows that firm size and profitability is significant negative to tax avoidance, firm's age does not signify positive to tax avoidance, and leverage has a significant positive effect on tax avoidance.Keywords: Tax avoidance, firm size, firm age, profitability and leverage